Pengaruh Struktur Modal, Likuiditas, dan Efisiensi Aset terhadap Profitabilitas pada Perusahaan Minyak & Gas Bumi yang Terdaftar di BEI Periode 2022-2024 - Made Yudi Tripramana; Ni Made Suci (Pusat Riset dan Inovasi Nasional, 2026)
The oil and gas sector plays a strategic role in national economic stability; however, global commodity price fluctuations often place significant pressure on corporate financial performance. This study was conducted to analyze the influence of capital structure, liquidity, and asset management efficiency on the profitability of oil and gas companies listed on the Indonesia Stock Exchange between 2022 and 2024. The research method employed is a quantitative approach using multiple linear regression analysis. Sampling was carried out through a purposive sampling technique across a population of 18 companies, resulting in 11 selected firms with a total of 29 observation data points after the removal of outliers. The results of the data analysis indicate that, partially, capital structure has a negative and significant influence on the company's ability to generate profit. In contrast, liquidity and asset efficiency variables were found to have no significant independent effect on profitability. Nevertheless, simultaneously, all independent variables contribute significantly to determining the company's profitability level, with a coefficient of determination of 21.7 percent. The implications of this research emphasize the importance for corporate management to exercise greater caution in determining debt policies and capital structures. Strict supervision of debt ratios is necessary to avoid interest burdens that could erode net income, particularly amidst global energy market uncertainty, to ensure long-term business sustainability.